UJI PERFORMANCE TURBIN CROSS FLOW Ã200 SEBAGAI SISTEM PEMBANGKIT LISTRIK TENAGA MIKROHIDRO - , Vickie Igor Romualdez Tampubolon, Dr.Sc.Tech. Adhy Kurniawan, S.T. ([Yogyakarta] : Universitas Gadjah Mada, 2011)
According to data from DJLPE in 2008, potential micro-hydro energy sources in Indonesia for 458.75 MW, while the newly installed capacity of 20.9 MW. Masters in Systems Engineering with a concentration of micro hydro UGM (Renewable Energy) is an educational institution in Indonesia that concern about the development of New and Renewable Energy (EBT). Activities of student interns concentration of micro hydro generation MST UGM 2008 conducted at the Laboratory of Mechanical Engineering Diploma generate a Cross Flow Turbine. This research aims to examine the characteristics of Cross Flow Turbine by microhydro MST UGM students of 2008 interns results as a system of microhydro power plant, conducted in the laboratory and in the Field is in the Dusun Bayeman, Turi, Sleman, Yogyakarta. Cross Flow Turbine test results in the laboratory showed that the maximum water discharge 0.0652 m 3 /s, effective head 0.7 m, turbine rotation 334 rpm, turbine torque of 0.22 Nm, turbine mechanical power 7.84 watts, and maximum turbine efficiency 18.89%. Test results on the MHPP Dusun Bayeman, Turi, Sleman, Yogyakarta is done without connecting the load, shows that the effective head 6.15 m, water discharge 0.045 m 3 /s, turbine rotation 450 rpm, turbine torque 7.924 Nm, mechanical power turbines 373.208 watts, water potential power 2714.92 watts, and turbine efficiency 13.75%. While the results of testing of turbines in the field associated with the induction motor 1 HP, 3Ï with 50 watt lamp load, produces a maximum induction motor output power 172.8 watts, turbine rotation 203 rpm, induction motor rotation 800 rpm, and total efficiency 6.36%. The results of economic analysis concluded that the project builder MHPP Dusun Bayeman not feasible using Cross Flow Turbine with 1 HP induction motor, 3Ï used for testing in this research, while the power potential available in the Dusun Bayeman feasible renovation project development MHP Bayeman Dusun with the calculation Break Event Point (BEP) for 4 years and 6 months after completion of the renovation project.